Good Knowledge Influences the Junior and Senior Pharmacy Students to Self-Medicate - Derar H. Abdel-Qader; Abdullah Albassam; Esra’ Taybeh; Nadia Al Mazrouei; Khalid Awad Al-Kubaisi; Rana Ibrahim; Reham Aljalamdeh; Salah Abdalrazak Alshehade; Ahmad Naoras Bitar; Salim Hamadi (International Journal of Medical Toxicology and Legal Medicine, 2022)
Background: Self-medication is a global health issue that requires thorough study and management due to its associated benefits and risks. This study aimed to investigate the prevalence and determinants of self-medication practices among first-year and fifth-year pharmacy students. Methods: A cross-sectional study was conducted, and data were collected from 229 students using pre-tested questionnaires. Results: The findings revealed that approximately three-quarters of pharmacy students with good knowledge practiced self-medication (75.9%). Senior students were found to be twice as likely to self-medicate compared to juniors (OR=1.92, 95%CI: 1.05:3.49), and self-medication practice was associated with academic level and gender. The most common health complaints that led to self-medication were headaches (86.3%) and the common cold (85.0%). The two primary reasons for self-medication were prior positive experiences (76.9%) and the availability of drugs at home (73.8%). Conclusion: It is crucial to acknowledge that self-medication practices can have benefits, but they should be done responsibly and with proper knowledge. Pharmacists play a critical role in promoting responsible self-medication practices as they are the primary source of drug information.